2023
DOI: 10.1002/mabi.202300169
|View full text |Cite
|
Sign up to set email alerts
|

Citronellol‐Based Long‐Lasting Antibacterial Cotton Fabrics without Bacterial Resistance

Abstract: Antibacterial cotton helps prevent the growth and spread of harmful microorganisms, reduces the risk of infection, and has a prolonged service life by reducing bacterial degradation. However, most antibacterial agents used are toxic to humans and the environment. Citronellol‐poly(N,N‐dimethyl ethyl methacrylate) (CD), a highly effective antibacterial polymer, is synthesized from natural herbal essential oils (EOs). CD exhibited efficient, rapid bactericidal activity against Gram‐positive, Gram‐negative, and dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…It has been discovered that borneol’s stereochemistry may play a role in regulating microbial adhesion . Bacteria are prevented from adhering to artificial surfaces made from bornyl-based homopolymers and copolymers. , Our group had previously developed a durable antibacterial and antifouling cotton fabric based on natural borneol and citronellol. , …”
Section: Introductionmentioning
confidence: 99%
“…It has been discovered that borneol’s stereochemistry may play a role in regulating microbial adhesion . Bacteria are prevented from adhering to artificial surfaces made from bornyl-based homopolymers and copolymers. , Our group had previously developed a durable antibacterial and antifouling cotton fabric based on natural borneol and citronellol. , …”
Section: Introductionmentioning
confidence: 99%
“…In this study, US and CT treatments alone showed limited killing effect of L. monocytogenes ( Table 1 ). In the study of Lian et al [34] , the poor water solubility and volatility of CT severely limited its antimicrobial activity. Similarly, Zhu et al [35] reported that the number of Staphylococcus aureus was reduced by only 0.48 log CFU/mL after 9 min of US (288 W, 20 kHz) treatment alone.…”
Section: Discussionmentioning
confidence: 99%
“…Agrawal et al [13] reported a facile synthesis technique for the fabrication of superhydrophobic antibacterial fabrics by employing fluorine-free silane coupling agents as cross-linkers for enhanced durability and antimicrobial effect. Lian et al [14] extended the practical application of EOs to antibacterial surfaces and fabrics, which is promising for use in personal care products and medical settings.…”
Section: Introductionmentioning
confidence: 99%